Iron deficiency: a modern primer to diagnosis and management. Issue 2 (10th March 2021) - Alexandre, Leo; Chan, Simon S.M.
Abstract : Purpose of review: Iron deficiency with anemia (IDA) and without anemia remain a diagnostic and management challenge. Iron deficiency has a broad spectrum of causes, including gastrointestinal malignancy. The purpose of this review is to summarize the value and limitations of current methods to diagnose iron deficiency and underline the relevance of contemporaneous evidence to guide the pretest probability of gastrointestinal disease. Recent findings: A number of biomarkers for iron deficiency exist, and all have their caveats. Serum ferritin remains the most pragmatic means of diagnosing iron deficiency. Hepcidin holds future promise as a marker of iron status during inflammatory states. Men and postmenopausal women with IDA have the highest overall prevalence of gastrointestinal malignancy (∼11%), while premenopausal women with IDA (<1.5%) and those with iron deficiency without anemia (<0.5%) have a very low risk. Noninvasive investigation with fecal immunochemical test and fecal calprotectin hold promise to guide further investigations in lower risk groups. Summary: Confirmation of iron deficiency remains a challenge. Appropriate risk stratification is the key to guiding judicious gastrointestinal investigation. Use of noninvasive tests may play an important role in lower risk groups. Risk prediction tools applicable to relevant populations are required.